PHYSICAL AND CHEMICAL SCARIFICATION ON DORMANCY BREAKING OF ROSARY PEA SEEDS (ABRUS PRECATORIUS L.) - Imam Safir Alwan Nurza (Bajang Institute, 2023)
Abstract: Seeds are part of the plant containing embryo that grows through the germination process. This process involves metabolism occurs in seeds to produce roots and shoots. However, this metabolic process is inhibited by the environment and genetics of the seeds itself. Thus, the seeds experience dormancy and fail to grow. Dormancy can be broken with help of physical and chemical scarification to accelerate seed germination. The research aim was to determine the physical and chemical scarification seed dormancy breaking in increasing the germination rosary pea seeds (Abrus precatorius L.). The research method used was experimental randomized block design using 4 treatment groups, namely cracked (F1), sanded (F2), and soaked in 50% H2SO4 solution for 15 minutes (K1) and 30 minutes (K2) and the group control with water. The viability germination, germination rate (GER), vigor index (VI), simultaneous growth (SG) normal sprouts on day 6, and growth rate (GOR) were observed for two weeks. The results obtained that immersion in H2SO4 50% solution for 30 minutes and cracking could break the dormancy of rosary pea seeds and increase germination with higher viability of germination, GER, VI, SG, and GOR than immersion in 50% H2SO4 solution for 15 minutes and sanding.